2006
DOI: 10.3201/eid1209.05-0979
|View full text |Cite
|
Sign up to set email alerts
|

1918 Influenza: the Mother of All Pandemics

Abstract: The "Spanish" influenza pandemic of 1918-1919, which caused approximately 50 million deaths worldwide, remains an ominous warning to public health. Many questions about its origins, its unusual epidemiologic features, and the basis of its pathogenicity remain unanswered. The public health implications of the pandemic therefore remain in doubt even as we now grapple with the feared emergence of a pandemic caused by H5N1 or other virus. However, new information about the 1918 virus is emerging, for example, sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
982
0
63

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 1,549 publications
(1,053 citation statements)
references
References 31 publications
8
982
0
63
Order By: Relevance
“…The significant and negative cross-correlation between deaths and births two months later may have been the result of stillbirths in the seventh month of gestation at the height of the pandemic. It is also possible that many women in the third trimester of pregnancy died during the pandemic, including (and perhaps especially) women who were in the seventh month of pregnancy, thus contributing to the birth trough observed two months after the mortality peak − a well-known fact about the age distribution of deaths during the 1918 pandemic period is the unusually high mortality rate among adults in the prime of life, including women of peak childbearing age (15−44 years old), forming a W-shaped age-specific death rate in contrast to the Ushaped distribution commonly observed in influenza epidemics (Noymer and Garenne 2000;Taubenberger and Morens 2006). In sum, the results suggest that, in addition to the two above observations, the mechanisms of reduced conceptions and embryonic losses in the first month of the first trimester of the pregnancy, rather than elevated embryonic losses in the late stage of the first-trimester, are the dominant ones linking mortality and fertility.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The significant and negative cross-correlation between deaths and births two months later may have been the result of stillbirths in the seventh month of gestation at the height of the pandemic. It is also possible that many women in the third trimester of pregnancy died during the pandemic, including (and perhaps especially) women who were in the seventh month of pregnancy, thus contributing to the birth trough observed two months after the mortality peak − a well-known fact about the age distribution of deaths during the 1918 pandemic period is the unusually high mortality rate among adults in the prime of life, including women of peak childbearing age (15−44 years old), forming a W-shaped age-specific death rate in contrast to the Ushaped distribution commonly observed in influenza epidemics (Noymer and Garenne 2000;Taubenberger and Morens 2006). In sum, the results suggest that, in addition to the two above observations, the mechanisms of reduced conceptions and embryonic losses in the first month of the first trimester of the pregnancy, rather than elevated embryonic losses in the late stage of the first-trimester, are the dominant ones linking mortality and fertility.…”
Section: Discussionmentioning
confidence: 99%
“…The 1918 influenza pandemic, variously known as the "mother of all pandemics" (Taubenberger and Morens 2006) for its impact on global population and the "forgotten pandemic" (Crosby 2003) for the relative lack of attention researchers have paid to it, is one of the "big three" pandemics in recorded history (Langford 2002;Patterson 1983). Demographic research on the subject has focused heavily on patterns of mortality, paying relatively little attention to the equally important phenomenon of fertility.…”
Section: Introductionmentioning
confidence: 99%
“…Years of occurrence all influenza pandemics from 1871 to 2015 and months of their peaks were obtained from the literature (Taubenberger and Morens, 2006;Richard et al, 2009;Bandaranayake et al, 2011;Kempinska-Miroslawska and Wozniak-Kosek, 2013;Mummert et al, 2013;Skog et al, 2014). Years of all El Niño events from 1871 to 2015 were obtained from the literature (Quinn and Neal, 1987) and Oceanic Niño index (National Oceanic Atmospheric Administration, 2015e).…”
Section: Datamentioning
confidence: 99%
“…The intervals between historical influenza pandemics have been estimated to vary from 10 to 50 years (Potter, 2001) and 6-149 years , unlike seasonal influenza epidemics, which occur annually during the winter of northern and southern hemispheres (Oluwole, 2015). Further, influenza pandemics peak multiple times, but the peaks are not restricted to winter seasons (Taubenberger and Morens, 2006). Although the basis for the timing of influenza pandemic waves are not established, it has been attributed to timing of school calendar, demography, geography, changes in virulence of influenza A viruses strains, and waning immunity (Mummert et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…With mortality rate being estimated as 61 deaths per 10 000 people due to the 1918 Spanish flu (all waves) in Canada, 15 about 50 000 Canadians died of the influenza and its complications during the pandemic. It was shown that the Spanish flu spread more or less in three distinct waves during about 12 month period in 1918–1919 simultaneously in Europe, Asia, and United States 29 . A more fatal pandemic influenza wave occurred in Canada in the fall and early winter of 1918–1919.…”
Section: Introductionmentioning
confidence: 99%